عبد الكريم قاسم والثورة الجزائرية (1958-1962م) - - زروق نبيلة (جامعة محمد بوضياف بالمسيلة, 2025)
يتناول هذا البحث التحوُّل الاستراتيجي في الموقف العراقي تجاه الثورة الجزائرية عقب قيام ثورة 14 تموز (جويلية)/يوليو 1958 وتولّي عبد الكريم قاسم زمام السلطة في العراق. إذ شهدَ هذا الموقف تغيُّراً جوهرياً من سياسةٍ تتسم بالحذر والتردُّد، ميزت العهد الملكي، إلى استراتيجية داعمة متكاملة ومتعددة الأبعاد للثورة الجزائرية.ارتكز هذا التحوّل على منظومة من المرتكزات الفكرية والسياسية، تمثلت في المبادئ التحررية المناهضة للاستعمار التي حملها المشروع الثوري لثورة 14 تموز (جويلية)، والانعتاق من قيود الارتباطات والتحالفات الغربية، والسعي نحو ترسيخ المكانة الريادية للعراق في النظام الإقليمي العربي. وقد تجلّى هذا الدعم في مظاهر متعددة ومتكاملة، اشتملت على الاعتراف المبكر بالحكومة الجزائرية المؤقتة، وتقديم الإسناد الدبلوماسي والسياسي في المحافل الدولية، وتوفير المساعدات المالية والعسكرية واللوجستية، وتفعيل الآلة الإعلامية وتعبئة الرأي العام.تميَّز موقف قاسم من الثورة الجزائرية بالثبات والاستمرارية طوال فترة حكمه، على الرغم من الضغوط الخارجية والتحديات الداخلية، مما جعل العراق في عهده أحد الداعمين الرئيسيين للثورة الجزائرية في العالم العربي. وعلى الرغم من أن سقوط نظامه في شباط/فبراير 1963 أدى إلى تحوُّل في طبيعة العلاقات العراقية-الجزائرية، إلا أن إرث هذه المرحلة ظل راسخاً في الذاكرة التاريخية للشعبين.يخلص البحث إلى أن مساندة عبد الكريم قاسم للثورة الجزائرية مثّلت أنموذجاً للتضامن العربي الفعّال في مواجهة الاستعمار، وعكست التوجهات الجديدة للسياسة الخارجية العراقية عقب ثورة 14 تموز (جويلية)، القائمة على مناصرة قضايا التحرر ومجابهة الهيمنة الاستعمارية This research examines the strategic transformation in Iraq's position toward the Algerian Revolution following the July 14, 1958 Revolution and Abd al-Karim Qasim's rise to power in Iraq. This position witnessed a fundamental shift from a policy characterized by caution and hesitation during the monarchical era to a comprehensive and multidimensional supportive strategy for the Algerian Revolution. This transformation was based on a system of intellectual and political foundations, represented by the anti-colonial liberation principles championed by the revolutionary project of the July 14 Revolution, the liberation from Western alliances and commitments, and the pursuit of consolidating Iraq's leading position in the Arab regional system.This support manifested in multiple and integrated aspects, including early recognition of the Provisional Algerian Government, providing diplomatic and political support in international forums, delivering financial, military, and logistical assistance, and activating media machinery and public opinion mobilization. Qasim's position on the Algerian Revolution was characterized by stability and continuity throughout his rule, despite external pressures and internal challenges, making Iraq under his leadership one of the main supporters of the Algerian Revolution in the Arab world.Although the fall of his regime in February 1963 led to a shift in the nature of Iraqi-Algerian relations, the legacy of this period remained firmly established in the historical memory of both peoples. The research concludes that Abd al-Karim Qasim's support for the Algerian Revolution represented a model of effective Arab solidarity in confronting colonialism and reflected the new orientations of Iraqi foreign policy following the July 14 Revolution, based on supporting liberation causes and confronting colonial hegemony.